Graphene composite profile prepared from brass waste, preparation process and application

Through powder metallurgy and medium-temperature continuous extrusion processes, graphene is fully extruded into the lattice void of brass waste, and high-performance graphene composite profiles are prepared, which solves the corrosion resistance of brass materials in corrosion and high-temperature environments, and realizes efficient recycling and utilization of brass waste.

CN119897469AActive Publication Date: 2025-04-29BEIJING JINPENG ZHENXING COPPER IND CO LTD

Patent Information

Application Number
CN202510399367.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-04-29
Estimated Expiration
2045-04-01

AI Technical Summary

Technical Problem

The problems of stress corrosion resistance, cavitation corrosion, high temperature corrosion in corrosive environments, high temperature corrosion in brass materials, as well as the problems of serious pollution, long production cycle and high production costs in brass production and waste recycling.

Method used

Through powder metallurgy combined with medium-temperature continuous extrusion process, graphene is fully extruded into the lattice void of brass waste, and high-strength, high thermal conductivity, high electrical conductivity, and high corrosion resistance graphene composite profiles are prepared.

Benefits of technology

It realizes efficient and pollution-free direct recycling of brass waste, improves the hardness, strength, conductivity, corrosion resistance and high-temperature creep resistance of composite materials, and reduces production cycle and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897469A_ABST
    Figure CN119897469A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of powder metallurgy, in particular to a preparation process of a graphene composite profile prepared from brass waste, which comprises the following steps: selecting the brass waste containing different components according to the application scene of the graphene composite profile; the brass waste materials are smashed into brass block-shaped smashed materials; the preparation method comprises the following steps: adding 0.001-10% by mass of graphene into the brass block-shaped crushed aggregates, and carrying out wet ball milling to form a first-size mixed powder liquid; carrying out semi-solid rotary shearing and stirring processing on the mixture; and continuously extruding the graphene-brass mixed base material to form a graphene composite profile blank, and carrying out post-process to obtain the graphene composite profile capable of overcoming brass spot, line and surface defects. According to the invention, a powder metallurgy process is combined with a medium-temperature continuous extrusion process, so that the brass waste is efficiently and directly recycled without pollution, and the physical properties and chemical properties such as hardness, strength, conductivity, corrosion resistance and high-temperature creep resistance of the composite material are greatly improved. The invention further correspondingly discloses the graphene composite profile and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder metallurgy, and in particular to a graphene composite profile prepared by using brass waste, a preparation process and an application thereof. Background Art

[0002] As an important nonferrous metal alloy, brass is widely used in many fields. Due to its good comprehensive properties, such as high strength, good processing performance and certain corrosion resistance, it is widely used in the manufacture of mechanical parts, electronic components, pipe fittings and other products.

[0003] Ordinary brass is mainly composed of electrolytic copper and electrolytic zinc, while complex brass is made by adding trace elements to ordinary brass to improve the physical and chemical properties of complex brass. The production of brass uses a large amount of electrolytic copper, electrolytic zinc, electrolytic aluminum, and electrolytic tin, which require the mining of ore, causing great damage to the environment. Since the mainstream production method is horizontal continuous casting and vertical casting, followed by rolling and drawing in the later stage, the production cycle is long and a large amount of waste gas, wastewater, dust, and waste slag will be generated during the production process. Due to the large difference in the melting points of copper, zinc and trace elements, especially zinc volatilizes violently at high temperatures. Volatile substances produce odor and dust, which seriously pollute the environment. Therefore, the factory needs to be equipped with special fume and dust collection devices, and clean the collection devices regularly. Since the zinc dust particles are fine, the cleaning work is time-consuming and laborious.

[0004] Due to the high melting temperature of CuZn alloy, the trace elements (Sn, Mn, Fe, P, Mg, Al, Ni, Si, rare earth and other trace elements) added in the complex brass production process have complex adding process, large loss of added elements, high difficulty, and serious segregation problems. It seriously affects the quality of brass plates, rods, strips, rows, wires and tubes. With the development of science and technology, special environments such as electrical control, high temperature and corrosion have higher and higher requirements on the performance of materials such as fatigue resistance, corrosion resistance, high conductivity and high fatigue resistance. Conventional brass profiles can no longer meet these requirements. In special environments such as ocean, humidity and outer space, suitable material solutions are scarce.

[0005] In addition, in order to improve the reuse of brass, there are currently two main ways to recycle brass waste: direct and indirect. However, whether it is to directly smelt high-quality copper waste into finished products, or to indirectly smelt copper waste into electrolytic copper and electrolytic zinc through electrolysis, it is inseparable from smelting, sulfide liquid preparation, and electrolytic purification processes. These processes will produce solid waste pollution, waste gas and waste slag, and waste liquid emissions.

[0006] Due to the scarcity of applicable material solutions in special environments such as the ocean, humidity, and outer space, in order to meet the production needs of new materials, the industry has conducted research through microalloying, adding rare earth elements and other solutions and achieved certain results. For example, our company's authorized invention patent with application number 202411661383.7 discloses a method and application of preparing graphene composite copper strips using copper waste, and specifically discloses that through powder metallurgy combined with medium-temperature continuous extrusion process, graphene is fully squeezed into the lattice gap of copper waste as a filling element, forming a high-performance graphene composite copper strip with high strength, high thermal conductivity and high electrical conductivity. This preparation method not only realizes the efficient and pollution-free direct recycling of copper waste, but also solves the recycling and production problems of copper waste by non-smelting methods.

[0007] On this basis, this application is specially proposed to solve the problems of stress corrosion resistance, cavitation corrosion, high temperature corrosion, reduced mechanical strength of brass materials in corrosive environments and high temperature environments, as well as the problems existing in brass production and waste recycling. Summary of the invention

[0008] In order to solve at least one of the above technical problems, the present invention proposes a method for preparing graphene composite profiles, preparation processes and applications by using brass waste through powder metallurgy combined with a medium-temperature continuous extrusion process, so as to solve the problems of serious pollution, long production cycle, high production cost and the failure of the performance indicators of the produced profiles to meet the use requirements in the non-smelting recycling and reuse of brass waste.

[0009] To achieve the above object, the present invention adopts the following technical solution: The first aspect of the present invention provides a graphene composite profile prepared by using brass waste, wherein the graphene composite profile is prepared by combining the brass waste with graphene through powder metallurgy and medium-temperature continuous extrusion process; The graphene composite profile comprises the following raw material components in percentage by mass: Cu: 45-97%, P: 0.001-0.4%, Fe: 0.01-1%, graphene: 0.001-10%, Zn: 3-49%, and the remainder is one or more of Ag, Au, Ni, Sn, Mn, and Al, and the total amount is less than 0.5%; Or, the graphene composite profile comprises the following raw material components in percentage by mass: Cu: 45-97%, Ag: 0.0001-0.1%, Fe: 0.01-1.5%, P: 0.001-0.4%, graphene: 0.001-10%, Zn: 3-49%, and the remainder is one or more of Ni, Fe, Au, Sn, Mn, and Al, and the total amount is less than 0.5%; Or, the graphene composite profile comprises the following raw material components in percentage by mass: Cu: 50-97%, Mn: 0.001-5%, Al: 0.001-7.5%, Fe: 0.01-1%, P: 0.001-0.4%, graphene: 0.001-10%, Zn: 3-49%, and the remainder is one or more of Ni, Sn, Ag, and Au, and the total amount is less than 0.5%; Or, the graphene composite profile comprises the following raw material components in percentage by mass: Cu: 50-90%, Ni: 0.01-45%, Fe: 0.01-2%, Mn: 0.01-14%, P: 0.001-0.4%, graphene: 0.001-10%, and one or more of trace elements Al, Si, S, Mg, Bi, As, Sb, Ag, and Au, with a total amount less than 0.5%, and the balance being Zn; Or, measured by mass percentage, the graphene composite profile contains the following raw material components: Cu: 50-97%, Fe: 0.1-1%, Sn: 0.01-5%, P: 0.001-0.4%, graphene: 0.001-10%, Zn: 3-49%, and the remainder is one or more of Mn, Au, Ag, Ni, and Al, and the total amount is less than 0.5%.

[0010] A second aspect of the present invention provides a process for preparing a graphene composite profile using brass waste, comprising the following steps: S1, selecting brass scraps containing different components according to the application scenarios of graphene composite profiles; S2, crushing the brass waste into brass block fragments; S3, according to the application scenario of the graphene composite profile, adding 0.001-10% by mass of graphene to the brass block fragments, and forming a first-size mixed powder liquid by wet ball milling; S4, subjecting the first-size mixed powder liquid to a semi-solid state rotation shear stirring process, so that the graphene is evenly filled in the brass fine crystal structure to form a graphene-brass mixed substrate; S5, heating the extrusion die cavity of the continuous extruder, and continuously extruding the graphene-brass mixed substrate when the graphene-brass mixed substrate is in a semi-liquid state, so that the graphene as a filling element is completely squeezed into the lattice gap of the brass fine-grained structure, forming a graphene composite profile blank that overcomes the point, line and surface defects of brass; S6, processing the graphene composite profile blank with reference to the subsequent process of conventional brass to obtain a graphene composite profile, wherein the graphene composite profile is subjected to continuous extrusion and subsequent processes to form a three-dimensional radial staggered structure for efficient electron transmission inside the structure.

[0011] Preferably, the size of the brass block fragments is 1-2 cm, and the particle size of the first-size mixed powder liquid is less than 50 μm.

[0012] Preferably, S4 comprises the following steps: S41, feeding the first-size mixed powder liquid into the front section of a circular feeder provided with an ultrasonic device, and performing a homogenization treatment on the first-size mixed powder liquid by utilizing the cavitation effect of the ultrasonic wave on the liquid; S42, feeding the first-size mixed powder liquid after homogenization treatment into the rear section of a circular feeder provided with a heating device, heating the circular feeder to 500-650° C. according to the copper content of the first-size mixed powder liquid, injecting inert gas into the rear section and keeping the temperature, so that the first-size mixed powder liquid reaches a semi-solid state to form a graphene-brass mixed substrate; S43, the graphene-brass mixed substrate is subjected to rotational shear stirring by the rotating mechanism of the twin screws of the circular feeder, the screw stirring speed is 10r-400r / min, and after stirring for 10-20min, it is transported to the discharge port of the circular feeder.

[0013] Preferably, the circular feeder is made of nickel-based high-temperature metal GH3044; the pushing pressure range of the twin-screw is 50-65 MPa, at which time, the density of the graphene-brass mixed substrate is more than 65% of the normal solid theoretical density.

[0014] Preferably, S5 comprises the following steps: S51, sending the graphene-brass mixed substrate into a continuous extruder; S52, according to the ratio of copper and zinc in the brass waste, the extrusion cavity temperature of the continuous extruder is set to 800-950° C., so that the copper alloy is in a semi-liquid state in the extrusion cavity, the extrusion pressure is set to not less than 1000 MPa, and the graphene-brass mixed substrate is continuously extruded to obtain the graphene composite profile blank.

[0015] Preferably, the continuous extruder is a Conform continuous extruder, and the extrusion die cavity is made of nickel-based high-temperature metal GH3044.

[0016] Preferably, the subsequent process of the brass profile includes rolling and drawing.

[0017] Preferably, the graphene composite profile is a graphene composite copper bar, a graphene composite copper plate, a graphene composite copper strip, a graphene composite copper rod, a graphene composite copper wire or a graphene composite copper tube.

[0018] The third aspect of the present invention provides a graphene composite profile prepared by the preparation process of the second aspect, which is applied to aircraft or consumer electronic connectors, data center connectors, new energy vehicle connectors or automotive circuit terminals or relays or electrical and electrical components that are conductive, elastic, and support components, or corrosion-resistant, highly elastic, and highly conductive components in corrosive and high-temperature environments.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses a powder metallurgy process combined with a medium-temperature continuous extrusion process to fully extrude graphene as a filling element into the lattice gaps of brass waste, forming a high-performance graphene composite profile with high strength, high thermal conductivity, high electrical conductivity, and high corrosion resistance that overcomes the point, line, and surface defects of brass. This preparation process directly recycles brass waste efficiently and pollution-free, and improves the physical and chemical properties of the composite material prepared from brass waste in terms of hardness, strength, electrical conductivity, corrosion resistance, and high-temperature creep resistance.

[0020] 2. This implementation adopts a continuous extrusion process. According to the ratio of copper and zinc in the brass waste, the extrusion cavity temperature of the continuous extruder is set to 800-950°C, and the extrusion pressure is set to not less than 1000Mpa. At this time, the solid-liquid ratio of the graphene-brass mixed substrate is less than 40%, and the arrangement of the elements in the graphene-brass mixed matrix is ​​disordered, and the semi-liquid graphene-brass mixed substrate is continuously extruded. Since the elements in the graphene-brass mixed substrate are multivariate, containing Zn, Ni, Fe and other elements (the main element of copper is Cu), through extrusion and subsequent rolling, drawing and other processes, graphene forms a fibrous three-dimensional radial staggered structure in the organization along the rolling and extrusion direction and the radial extension direction (graphene in the copper composite material only forms a linear extension organization along the rolling and extrusion direction). The three-dimensional fibrous radial interlaced structure constitutes an efficient transmission channel for electrons, effectively improving the conductivity of the composite material. At the same time, it also effectively reduces the potential difference between the elements in the matrix, eliminates the galvanic cell reaction between the elements of the graphene-brass mixed matrix, improves the dezincification corrosion problem of the brass material itself, and effectively improves the corrosion resistance of the graphene-brass composite material.

[0021] 3. The present invention uses brass scraps containing different components to effectively solve the problem of continuous recycling of brass scraps in society, while significantly reducing the production cycle of brass profiles, achieving low energy consumption, efficient use of waste brass scraps to produce high-performance composite copper profiles without the emission of waste water, waste slag, and waste gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The present invention is a process flow chart of a graphene composite profile prepared from brass waste. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. It is obvious that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments of the present invention.

[0024] Embodiment 1

[0025] Please refer to Figure 1 A preparation process of a graphene composite profile prepared by using brass waste comprises the following steps: S1, according to the application scenario of graphene composite profiles, brass scraps containing different components are selected.

[0026] It should be noted that the purpose of selecting brass scraps containing different components is to prepare graphene composite copper strips with different physical and chemical properties by screening brass scraps with different components through the following preparation process. Specifically, the physical properties include but are not limited to high electrical conductivity, high thermal conductivity, high strength, high toughness and high specific surface area. The chemical properties include but are not limited to corrosion resistance, oxidation resistance and heat resistance.

[0027] Compared with the traditional production process of existing brass profiles, such as horizontal continuous casting and vertical casting process, in order to enhance the physical or chemical properties of brass profiles, it is necessary to add trace elements such as Sn, Mn, Fe, P, Mg, Al, Ni, Si, rare earth, etc. The addition process is complicated, the loss of added elements is large, the difficulty is high, and various segregation problems are serious, so that the quality of the brass profiles cannot be guaranteed.

[0028] The present invention adopts brass scraps containing different components to effectively solve the problem of continuous recycling of brass scraps in the society. At the same time, the following preparation process is adopted to significantly reduce the production cycle of brass profiles, and achieve the purpose of low energy consumption and efficient utilization of waste brass scraps to produce high-performance composite copper profiles without the emission of waste water, waste slag or waste gas.

[0029] S2, crushing the brass waste into brass block fragments.

[0030] It should be noted that the brass scraps in this embodiment are crushed by a metal crusher. In order to facilitate the subsequent ball milling of the brass block fragments into powders of a specified particle size, the size of the brass block fragments in this embodiment is controlled to be 1-2 cm.

[0031] S3, according to the application scenario of the graphene composite profile, add 0.001-10% by mass of graphene to the brass block fragments, and form a first-size mixed powder liquid through wet ball milling.

[0032] It should be noted that the organic solvent added in the above-mentioned wet ball milling process is alcohol (such as anhydrous ethanol). Specifically, according to the ratio of graphene and brass, an appropriate amount of anhydrous ethanol is added, and at the same time, a certain number of ball milling balls (the ball milling balls can be made of zirconium oxide) are added, and the speed and ball milling time of the ball mill are set for ball milling. In this embodiment, the speed of the ball mill is set to 300-500r / min, and the time is 3-6 hours. In this embodiment, a large industrial ball mill is used, and the particle size of the solid in the first size mixed powder liquid is less than 50μm.

[0033] It can be understood that by ball milling the brass block fragments using a ball mill, the graphene and the brass block fragments can be evenly mixed, which helps to improve the physical and chemical properties of the composite material formed by the two to play a synergistic role.

[0034] The wet ball milling with ethanol added in this embodiment has at least the following advantages: 1. Good dispersibility and reduced surface tension: Anhydrous ethanol is a good organic solvent that can effectively reduce the surface tension between graphene and copper powder, making the dispersion of graphene in copper powder more uniform and avoiding the agglomeration of graphene. At the same time, anhydrous ethanol can improve the wettability of graphene and copper powder, making the two better mixed, thereby improving the uniformity of the composite material.

[0035] 2. Protect graphene structure and reduce defects during ball milling: During wet ball milling, anhydrous ethanol as a medium can buffer the direct impact between the ball milling ball and graphene, reduce the structural defects of graphene, and maintain its integrity. Compared with dry ball milling, the graphene obtained by wet ball milling is larger in size, has fewer defects, and has a more complete crystal structure.

[0036] 3. Enhance the bonding and adhesion between graphene and copper atoms: Anhydrous ethanol can help graphene adhere better to the surface of copper powder during the ball milling process, enhance the bonding between the two, and thus form a more uniform composite material in the subsequent sintering or densification process.

[0037] 4. Green and pollution-free: Anhydrous ethanol is a relatively environmentally friendly solvent. The wet ball milling process using anhydrous ethanol as a medium will not pollute the environment. At the same time, anhydrous ethanol can evaporate quickly under high temperature and is easy to remove.

[0038] 5. Improve material properties and mechanical properties: The mechanical properties of graphene copper composites prepared by wet ball milling are significantly improved. For example, the yield strength is increased by 219.8% compared with pure copper, and it has good ductility and conductivity. The uniform dispersion of graphene in the copper matrix can effectively improve the conductivity of the composite material.

[0039] 6. Inhibit oxidation: Due to the presence of a large amount of zinc in brass, during the ball milling process, the powder temperature rises and is prone to oxidation reaction with oxygen in the air. Anhydrous ethanol can form a protective film on its surface, isolating the air and reducing the contact between oxygen and brass. Thus, the oxidation of brass can be inhibited to a certain extent.

[0040] In addition, during the ball milling process, the brass scraps and graphene are continuously stirred, collided, and ball milled in the high-speed rotating ball mill. During this process, the brass alloy powder (first size mixed powder liquid) is repeatedly deformed, cold welded, and broken, and at the same time, the graphene sheets are also peeled off. Obvious atomic diffusion and solid-state reaction occur inside the brass alloy powder structure. Under the action of the external force of ball milling, a large number of organizational vacancies, dislocations, grain boundaries, and phase boundaries are generated inside the broken particles, providing channels and positions for the embedding of graphene.

[0041] The above defects will lead to an increase in deformation energy storage in the lattice. When the deformation energy storage is greater than the formation free energy required for the supersaturated solid solution, the solid solubility of graphene as the second phase in the matrix in this embodiment will be improved. At the same time, the heat generated during the ball milling process and the interface interaction between brass and graphene also contribute to the solid solution of graphene in brass. The interatomic forces at the interface promote the formation of certain chemical bonds between graphene and brass atoms, thereby enhancing the solid solution stability of graphene in brass.

[0042] In addition, the above defects will reduce the diffusion energy of the CuZn alloy, generate a large number of new surfaces, and create good physical conditions for the high-temperature hard point element graphene to form a coating and filling on the surface and inside of the following fine-crystallized CuZn alloy element.

[0043] Therefore, based on the solid solution mechanism of brass and graphene, this embodiment adjusts and prolongs the ball milling time, ball milling speed and ball-to-material ratio to increase the solid solubility, thereby improving the material properties of the solid solution. In addition, the amount of graphene input in this embodiment is also set based on the above solid solution mechanism. Adding excessive graphene is likely to cause agglomeration, reducing the solid solubility of graphene in brass.

[0044] S4, subjecting the first-size mixed powder liquid to a semi-solid state rotational shear stirring process, so that the graphene is evenly filled in the brass fine-grained structure to form a graphene-brass mixed matrix.

[0045] In order to improve the uniformity of the first-size mixed powder liquid and the uniformity of graphene filling, the feeding tube of the circular feeder in this embodiment adopts a circular feeding tube equipped with a relatively rotating twin screw, and at the same time, the circular feeding tube adopts a two-stage design. Specifically, the first-size mixed powder liquid after wet ball milling is fed into the front section of the circular feeder equipped with an ultrasonic device, and the first-size mixed powder liquid is homogenized by using the cavitation effect of ultrasonic waves on the liquid, so that the various tissues in the first-size mixed powder liquid are further evenly dispersed, preventing the precipitation of heavy elements, and at the same time, strengthening the surface adhesion of graphene and copper atoms.

[0046] In this embodiment, the ultrasonic frequency is 30-45KHz, and the time for the first-size mixed powder liquid to pass through the front section of the circular feeding pipe is set at 3-5min to ensure that the ultrasonic wave fully and evenly disperses the first-size mixed powder liquid.

[0047] Considering the need to perform semi-solid treatment on the first-size mixed powder liquid, a heating device is provided at the rear section of the circular feeding tube in this embodiment. According to the copper content of the first-size mixed powder liquid, the temperature in the circular feeding tube is raised to 500-650°C by the heating device, and the temperature is kept, so that the first-size mixed powder liquid is in a semi-solid state. At the same time, the graphene-brass mixed substrate is sheared and broken by the relatively rotating twin screws to obtain a fine-grained structure of brass. In this embodiment, the screw stirring speed is 10r-400r / min, and the stirring time is 10-20min.

[0048] In order to avoid the occurrence of oxidation reaction, in this embodiment, inert gas is injected into the rear section through the gas input port provided at the rear section of the circular feeding pipe. At the same time, the high-temperature evaporated anhydrous ethanol gas is extracted through the gas discharge port provided at the circular feeding pipe.

[0049] It is understandable that in the semi-solid crystallization state, the semi-solid metal alloy has typical rheological characteristics, and the deformation shear stress in the crystal structure is closely related to the ratio of the solid phase volume and the growth morphology. Specifically, when the solid phase volume ratio in the brass crystal structure reaches more than 15%, the solid phase begins to show dendrites and the metal begins to solidify.

[0050] At this time, the crushing, shearing and stirring mechanical vibrations generated by the high-speed rotating double-screw mechanism and the relative rotation of the double screws will cause relative movement between the liquid phase and the solid phase. Through the flow of liquid metal, the columnar and dendritic crystals in the organizational structure of the graphene-brass mixed substrate are effectively broken, limiting the continued growth of the recrystallized organization.

[0051] In addition, the crushing shear stirring mechanical vibration also has the effect of fine crystal organization proliferation and grain refinement. The high specific surface area (2600m2 / g) of the ball-milled graphene makes the graphene more evenly and stably distributed in the semi-solid organization, improving the physical and chemical properties of the graphene in the organizational structure. This is in preparation for the continuous extrusion preparation of graphene composite profiles.

[0052] Considering that the semi-solid graphene-brass mixed substrate may undergo an oxidation reaction with oxygen in the air, inert gas, specifically argon gas, is injected into the circular feeder in this embodiment.

[0053] In addition, injecting argon into the circular feeder can effectively control the oxygen content in the circular feeder, thereby ensuring that the oxygen content in the tissue structure is effectively controlled.

[0054] In order to ensure that the density of the semi-solid structure can reach more than 65% of the normal solid theoretical density, the pushing pressure range of the twin screw in this embodiment is 50-65MPa. Under this pressure, the density of the semi-solid structure (graphene-brass mixed substrate) will reach more than 65% of the normal solid theoretical density, thereby ensuring the initial formation of the structure and the stability of the formed crystalline structure.

[0055] It should be noted that since the inside of the round feeder needs to be heated to 500-650°C, the material of the round feeder must have sufficient high temperature strength and hardness, high tempering temperature resistance, good heat resistance, good machining properties, good material toughness, low thermal expansion coefficient and good thermal conductivity.

[0056] Based on the above factors, the circular feeder in this embodiment adopts nickel-based high-temperature metal GH3044.

[0057] Specifically, nickel-based high-temperature metal GH3044 has at least the following advantages: 1. High temperature resistance The theoretical high temperature resistance limit of GH3044 alloy can reach 1000℃. Under extreme high temperature conditions such as 1100℃, an extremely dense oxide film will quickly form on the surface of GH3044 alloy, effectively preventing oxygen from further contacting the interior of the alloy, thereby greatly slowing down the oxidation process.

[0058] At the same time, GH3044 alloy can still maintain high strength in high temperature environment, with a tensile strength of 650MPa at 1000℃, and has excellent creep resistance, for example, the creep rupture strength is 400MPa at 850℃. Therefore, GH3044 alloy products can operate stably in harsh environments of high temperature and high pressure. 2. Anti-oxidation and corrosion resistance GH3044 alloy contains high content of chromium (Cr), tungsten (W) and small amounts of molybdenum (Mo) and aluminum (Al). In a high-temperature oxidizing environment, these elements work together to form a dense oxide film on the alloy surface. Chromium can react with oxygen first to generate stable chromium oxide, which builds the first protective barrier for the alloy; the addition of tungsten enhances the stability and density of the oxide film; molybdenum and aluminum further optimize the structure of the oxide film, enhance its protective performance, and significantly improve the alloy's antioxidant properties.

[0059] In terms of corrosion resistance, the alloy exhibits good tolerance to highly corrosive media such as chlorine, sulfur, and nitrogen. In an oxidation test at 1100°C, the oxidation rate of GH3044 is only about , showing good antioxidant capacity. 3. Chemical composition and physical properties The main chemical composition of GH3044 is as follows: Nickel (Ni) as the matrix of the alloy provides a good comprehensive performance foundation for the alloy. The balance is: the chromium (Cr) content is 23.5-26.5%, which is a key element for forming an anti-oxidation film. The tungsten (W) content is 13.0-16.0%, which contributes significantly to improving the high temperature strength and anti-oxidation performance of the alloy; the titanium (Ti) content is 0.30-0.70%, which helps to optimize the organizational structure of the alloy; the iron (Fe) content is ≤4.0%, the aluminum (Al) content is ≤0.50%, the silicon (Si) content is ≤0.80%, the manganese (Mn) content is ≤0.50%, the phosphorus (P) content is 0.013%, the sulfur (S) content is 0.013%, the molybdenum (Mo) content is ≤1.50%, and the carbon (C) content is ≤0.10%. In terms of physical properties, its density is 8.89g / cm³, and its melting point ranges from 1352-1375℃. Its thermal conductivity ranges from 100-900℃. Gradually changes to The linear expansion coefficient is within the range of 20-900℃. After solution treatment at 1200℃, the alloy presents a structure mainly of single-phase austenite, and carbides at the grain boundaries are distributed in chain-like form. This unique microstructure further enhances its high-temperature stability. Based on the above advantages and characteristics, GH3044 nickel-based high-temperature alloy can maintain good performance in a high temperature environment of 1100°C with its excellent high-temperature strength, oxidation resistance and stability. In addition, the material has good stamping and welding process performance, making it easy to form and connect during processing. For this reason, it has become an ideal high-temperature material for making high-temperature equipment, key components in the energy field, reactors and pipelines in the chemical industry, and high-temperature processing equipment for non-ferrous metals.

[0060] The circular feeder made of GH3044 high-temperature alloy and the extrusion die cavity of the continuous extruder used in this example can meet the needs of long-term, high-temperature and high-speed stirring and vibration, and fundamentally solve the problem of stability and life of long-term operation of processing equipment in high-temperature environment.

[0061] S5, heating the graphene-brass mixed substrate, and continuously extruding the graphene-brass mixed substrate when the graphene-brass mixed substrate is in a semi-liquid state, so that the graphene as a filling element is completely squeezed into the lattice gap of the brass fine crystal structure to form a graphene composite profile blank that overcomes the point, line and surface defects of the brass.

[0062] Specifically, in this embodiment, a Conform continuous extruder is used to extrude the graphene-brass mixed substrate. At the same time, in order to ensure that the graphene retains a complete organizational structure when the copper substrate is melted, the extrusion die cavity temperature of the Conform continuous extruder in this embodiment is set to 800-950°C.

[0063] It should be noted that the brass waste recycled by the society mainly includes copper-zinc binary brass, tin brass, aluminum brass, iron brass, manganese brass, nickel brass, lead brass and some arsenic brass, as well as complex brass waste with silver, gold, tin and nickel plating on the surface.

[0064] The components of brass scrap mainly include Cu, Zn, Ag, γ-Fe (912°-1394°), Au, Sn, Al, Ni and other elements. The lattice composition of the above elements is face-centered cubic lattice, among which Zn is close-packed hexagonal lattice. The number of atoms in a single unit cell of the known face-centered cubic lattice and close-packed hexagonal lattice is 12.

[0065] The compactness of atomic stacking in a crystal is usually measured by "density". According to the density of atomic stacking, the face-centered cubic crystal plane and the close-packed hexagonal crystal plane are both atomic planes with the most compact arrangement of atoms of equal diameter. The atomic arrangement rules are exactly the same.

[0066] It is known that density refers to the ratio of the total volume occupied by atoms in a unit cell to the total volume of the unit cell, that is, the density formula is K=nv / V; Where: K--crystal density; N--The number of atoms actually contained in a unit cell: v--the volume of an atom (rigid sphere), its value is 4πR 3 / 3 (R is the atomic radius); V – total volume of unit cell.

[0067] From the above, we can know that the face-centered cubic density is: 0.74.

[0068] The density of hexagonal close-packed is: 0.74.

[0069] Among them, a and c are the edge lengths of the unit cell, also called lattice constants, and in hexagonal close-packed crystals c / a=1.633.

[0070] From this, we can see that the voids in the lattice of elements such as Cu (atomic diameter 0.255nm), Ag (atomic diameter 0.288nm), Au (atomic diameter 0.278nm), Al (atomic diameter 0.286nm), Ni (atomic diameter 0.248nm), Zn (atomic diameter 0.278nm), and γ-Fe (912°-1394°, atomic diameter 0.254nm) are 26%.

[0071] Since the element radius of graphene is small (the atomic diameter of C is 140pm under normal circumstances), which is much smaller than the atomic diameter of the above elements, combined with the principle of copper alloy intermetallic compounds, normal valence compounds are composed of elements that are far apart on the periodic table and have a large difference in electronegativity. Metal elements and compounds formed by non-metals in groups IVA, VA, and VIA in the periodic table. The filler element graphene used in this embodiment belongs to group IVA elements, so it can form compounds with metal elements in brass waste.

[0072] Based on the above factors, in order to ensure that graphene as a filling element can be completely squeezed into the 26% voids of the face-centered cubic lattice of Cu (atomic diameter 0.255nm), Ag (atomic diameter 0.288nm), Al (atomic diameter 0.286nm), Ni (atomic diameter 0.248nm), Zn (atomic diameter 0.278nm), and γ-Fe (912°-1394°, atomic diameter 0.254nm), solute atoms are formed, and strengthening is carried out from within the element unit cell. A dispersed filling and coating phase is formed around the original hard crystal core in the matrix, thereby forming a high-strength and high-conductivity filler.

[0073] This embodiment adopts a continuous extrusion process. According to the ratio of copper and zinc in the brass waste, the extrusion cavity temperature of the continuous extruder is set to 800-950°C, so that the copper alloy is in a semi-liquid state in the extrusion cavity, and the extrusion pressure is set to not less than 1000Mpa. The graphene-brass mixed substrate is continuously extruded to obtain a graphene composite profile blank.

[0074] At this time, the solid-liquid ratio of the graphene-brass mixed matrix is ​​less than 40%, and the arrangement of the elements in the graphene-brass mixed matrix is ​​disordered. At the same time, since the elements in the graphene-brass mixed matrix are multivariate, containing Zn, Ni, Fe and other elements (the main element of copper is Cu), through extrusion and later rolling and drawing processes, graphene forms a fibrous three-dimensional radial staggered structure in the organization along the rolling and extrusion direction and the radial extension direction (graphene in the copper composite material only forms a linear extension organization along the rolling and extrusion direction). These fibrous three-dimensional radial staggered organizations constitute an efficient transmission channel for electrons, effectively improving the conductivity of the composite material, and also effectively reducing the potential difference between the elements in the matrix, eliminating the primary battery reaction between the elements of the graphene-brass mixed matrix, improving the dezincification corrosion problem of the brass material itself, and effectively improving the corrosion resistance of the graphene-brass composite material.

[0075] After the above process, we can obtain a graphene composite brass blank. The process in this embodiment can be used to prepare a graphene composite profile in combination with subsequent rolling, drawing and other processes. Among them, the graphene composite profile includes but is not limited to a graphene composite copper bar or a graphene composite copper plate or a graphene composite copper strip or a graphene composite copper rod or a graphene composite copper wire or a graphene composite copper tube. Among them, the specifications of the graphene composite copper bar, plate, and strip can be a thickness of 1-25mm and a width of 5-600mm; the diameter of the graphene composite rod, wire, and tube can be 1-200mm.

[0076] At the same time, it should be particularly noted that the preparation process of the present invention can also be used for the preparation of composite profiles of copper scrap with a graphene addition amount of less than 0.1% and aluminum-based composite profiles with a graphene addition amount of 0.001-10%.

[0077] It should be noted that existing brass has point, line and surface defects. Based on the above defects, the brass alloy will have various problems in the prepared profiles, such as excessive resistance, severe high-temperature creep, reduced critical shear stress during complex bending, excessive material strength, reduced plasticity and increased brittleness, which seriously restrict the production and use of complex brass alloys.

[0078] The preparation process of the present invention can fundamentally solve the above-mentioned point, line and surface defects. Specifically: 1. Point defects Point defects: including vacancies and interstitial atoms. A vacancy refers to an atomic position in a crystal that is not occupied by an atom, forming an empty lattice position. An interstitial atom refers to an atom that enters the normal lattice gap position in the crystal.

[0079] Based on the above defects, this preparation process adds highly conductive graphene (whose conductivity is , the highest among known materials at room temperature), forming a uniformly distributed graphene filler in the material matrix. Under the continuous extrusion of medium temperature and pressure, the hard graphene nucleus is squeezed into the unit cell of the tissue crystal, and the replacement of substitutional solid solution atoms and interstitial solid solution atoms is realized in the matrix, thereby forming new high-conductivity and high-strength graphene solute atoms. Graphene solute atoms reduce the voids in the structure and improve the instability of the structure caused by the displacement of the original replacement atoms. At the same time, graphene with high strength and modulus fills the lattice voids, limiting the relative sliding of the brass matrix atoms. When the material is subjected to shear force, graphene can bear part of the load, which enhances the material's ability to resist shear deformation, and the macroscopic performance is an increase in shear modulus. In addition, from the perspective of electronic structure, the large π-bond electron cloud of graphene overlaps with the electron cloud of copper and zinc atoms, changing the distribution state of electrons and causing changes in the conduction path of electrons in the entire system. The electrons that were originally conducted in the brass matrix form new transmission channels due to the presence of graphene, thereby optimizing the electron conduction efficiency and improving the electrical conductivity of the material. At the same time, the vacancy concentration of the CuZn alloy is reduced by utilizing the high melting point of graphene and the high formation energy of Fe, Ni, and Mn elements, fundamentally improving the problems of low conductivity and severe high-temperature creep caused by point defects.

[0080] 2. Line defects Line defects are characterized by dislocation phenomena. Through analysis, it is found that when copper and zinc are used as the base material and diversified elements are added, dislocation phenomena will appear inside the base material due to the different elastic moduli of each metal atom. The existence of dislocation phenomena will seriously affect the shear stress resistance of the material.

[0081] In multi-element alloys, there are often multiple crystal structures. The shear stress of grains with different orientations is also different. When a dislocation occurs, the number of slip systems that meet the starting conditions will also be different. The shear stress of element grains that can improve dislocations is also relatively large. When the material undergoes plastic deformation, more slip system elements means that the material has good plastic deformation. At the same time, when a dislocation occurs, a stress field will inevitably occur around the dislocation.

[0082] Based on the above defects and formation factors, this preparation process adds graphene, utilizes the high strength (tensile strength 130GPa) and high toughness of graphene elements, and squeezes and fills them into the matrix unit cell to restrain and block the movement of dislocations.

[0083] Through experiments, it is known that stress fields will be generated around the dislocation site and the added graphene elements. The dislocation and the graphene solute atoms show elastic interactions. As solute atoms, graphene will be redistributed in the crystal under elastic interactions. Graphene will tend to the lowest energy position near the dislocation to form solute atom clusters around the dislocation. The solute atom clusters have a huge obstacle to the movement of dislocations, increasing the dislocation density and refining the grains. The dislocation slip of the brass alloy changes from plane slip to cross slip mode, and finally achieves solid solution strengthening, completely blocking the occurrence of dislocations from the matrix and solving the problem of line defects. Thereby, the critical shear stress of the graphene composite brass alloy during complex bending and the critical shear stress of the material are improved, so that it has excellent characteristics of high strength, high ductility, high plasticity and low rebound during molding.

[0084] 3. Surface defects The surface defects of brass are mainly characterized by grain boundaries. In a crystal, if two adjacent parts have different orientations, compositions, lattice types and lattice constants, there will be an interface at their contact. In a single-phase metal or alloy, the interface between adjacent grains with different orientations is called a grain boundary. Brass is a copper-zinc alloy. During its solidification and processing, a large number of grain boundaries will be formed due to the differences in the orientation of atoms in different regions.

[0085] Based on the above defects and formation factors, this preparation process makes full use of high-temperature hard points to form refined crystal nuclei, so that high-strength graphene particles are evenly distributed in the organizational structure. Through low-temperature stirring technology, copper dendrites are broken, and the growth of copper recrystallized grains is restricted, so that they form fine crystals around high-temperature hard crystal nuclei. At the same time, the high-strength dispersed particles of graphene elements formed by uniform distribution and then medium-temperature extrusion are filled into the unit cells of the crystal nucleus. The high conductivity and high strength of graphene significantly reduce the surface energy of the material, fundamentally solve the surface defects generated on the surface of the material, and improve the problems of excessive material strength, reduced plasticity, and increased brittleness.

[0086] The present invention uses a powder metallurgy process combined with a medium-temperature continuous extrusion process to fully extrude graphene as a filling element into the lattice gaps of brass waste, thereby forming a high-strength, high-thermal-conductivity, high-electrical-conductivity, and high-corrosion-resistant graphene composite copper strip that overcomes the point, line, and surface defects of brass. This preparation process directly recycles brass waste efficiently and pollution-free, and improves the physical and chemical properties of the composite material prepared from brass waste in terms of strength, conductivity, corrosion resistance, high-temperature resistance, and wear resistance.

[0087] Embodiment 2

[0088] It should be noted that the same process and the same components in the preparation process of brass waste under the same process conditions have the same or similar performance effects on the graphene composite profile, which will not be repeated in this embodiment and the following embodiments.

[0089] Different from Example 1, in this embodiment, the brass scrap contains the following raw material components in mass percentage: Cu: 45-97%, P: 0.001-0.4%, Fe: 0.01-1%, graphene: 0.001-10%, Zn: 3-49%, and the remainder is one or more of Ag, Au, Ni, Sn, Mn, and Al, and the total amount is less than 0.5%.

[0090] Based on the above-mentioned component content requirements, the brass scraps selected in this embodiment are copper, zinc, and unplated stamping scraps generated after stamping of electrical and electronic parts, automobile waste wiring harnesses (with brass tinned terminals), waste wires and cables, and unplated scrap brass recycled from the society.

[0091] Brasses with different CuZn contents were tested and compared, and some grades of comparison data are shown in the following table:

[0092] From the test results in the above table, it can be seen that the yield strength of different CuZn substrates with added graphene is increased by 142%, the tensile strength is increased by 23%, the Vickers hardness is increased by 27.6%, and the elastic modulus is increased by 4.48%.

[0093] Embodiment 3

[0094] Different from the above embodiment, in this embodiment, the graphene composite profile contains the following raw material components in percentage by mass: Cu: 45-97%, Ag: 0.0001-0.1%, Fe: 0.01-1.5%, P: 0.001-0.4%, graphene: 0.001-10%, Zn: 3-49%, and the remainder is one or more of Ni, Fe, Au, Sn, Mn, and Al, and the total amount is less than 0.5%.

[0095] Based on the above-mentioned component content requirements, the brass waste materials selected in this embodiment are copper, zinc and gold-plated, silver-plated and copper-plated brass scraps recycled from the society as raw materials.

[0096] In this embodiment, the Ag element is used to enhance the pinning effect of the strengthening phase in the CuZn, CuFe, and CuSn alloys of the microstructure, and the grain size can be refined while enhancing the bonding strength between Zn and Fe atoms and Cu atoms, thereby significantly increasing the number of crystal nuclei in the microstructure, increasing the density of the material, effectively improving the critical shear stress of the lattice in the microstructure, and reducing the probability of dislocation occurrence.

[0097] Experiments show that compared with H96 ordinary brass material, the resistivity of the composite material with 0.02% graphene and 0.01% Ag is reduced by 8%. , down to The elastic modulus increased by 6.6%, from 115GPa to 122GPa, and the conductivity increased by 8%, from the original 54%IACS to 58%IACS.

[0098] The composite material prepared in this embodiment can fully solve the problem of high conductivity, high strength and high electrical conductivity in the fields of automotive wiring harnesses, chip frame materials and connectors. Not only that, the material also significantly reduces production costs, effectively extends the service life of automobiles, chip frames and connectors, successfully overcomes the problem of signal attenuation during signal transmission, and reduces the failure rate of new energy vehicle signal transmission and high-power connector operation. Due to its high conductivity, the temperature rise problem of high-power chips and connectors can be completely solved, the power reduction problem caused by resistance value problems is also effectively improved, and the loss problem in signal transmission can be completely eliminated.

[0099] Embodiment 4

[0100] Different from the above embodiment, in this embodiment, the graphene composite profile contains the following raw material components in percentage by mass: Cu: 50-97%, Mn: 0.001-5%, Al: 0.001-7.5%, Fe: 0.01-1%, P: 0.001-0.4%, graphene: 0.001-10%, Zn: 3-49%, and the remainder is one or more of Ni, Sn, Ag, and Au, and the total amount is less than 0.5%.

[0101] Based on the above-mentioned component content requirements, the brass waste selected in this embodiment is manganese brass and aluminum brass waste recycled from the society, a certain amount of iron-containing C194 and C192 frames are added, and scraps are recycled. Production is carried out through the above-mentioned preparation process, the main purpose of which is to solve the problem of high temperature corrosion resistance of brass materials.

[0102] The following factors are known to cause corrosion of brass: 1. Oxidative corrosion of brass in high temperature air generates copper oxide (CuO) and zinc oxide (ZnO). These oxides will form a loose oxide layer, with ZnO on the inner surface and CuO on the outer surface. The protective effect of the oxide layer is poor and cannot effectively prevent further oxidative corrosion.

[0103] 2. Dezincification corrosion: In high temperature environment, the zinc element in brass is more likely to volatilize or be oxidized, resulting in a decrease in the zinc content in the alloy and an imbalance in the copper-zinc ratio, thus causing dezincification corrosion. After dezincification, the mechanical properties and corrosion resistance of brass will be significantly reduced.

[0104] 3. Stress corrosion cracking: Brass is prone to stress corrosion cracking in a high-temperature environment containing ammonia or chloride. This is because at high temperatures, ammonia or chloride will react with copper, zinc and other elements in brass to generate stress concentration-sensitive compounds. At the same time, high temperatures will increase the stress level of the material, leading to the formation and expansion of cracks.

[0105] Based on the above-mentioned corrosion factors of brass, this example can form a FeMn alloy by adding Mn elements. Through precipitation strengthening of the FeMn alloy, without affecting the conductivity, not only the mechanical properties and corrosion resistance of the FeMn alloy are effectively improved, but also the eddy current corrosion resistance of the substrate is significantly improved.

[0106] At the same time, by adding Al elements, high-strength hard points are formed in the matrix. Since the standard potential of aluminum is more negative than that of zinc, it preferentially combines with oxygen in the environment to form a dense and hard aluminum oxide film on the surface of the graphene material. , significantly improving the strength and corrosion resistance of brass.

[0107] Experiments have shown that the graphene composite material obtained by adding graphene and Mn and Al elements through powder metallurgy and medium-temperature extrusion, under high temperature of 200° and chlorine-containing environment conditions, did not show dezincification, stress corrosion, oxidation discoloration, and changes in organizational structure on the surface of the graphene composite material for 4 hours.

[0108] In the automotive standard neutral salt spray test of no less than 96 hours, the graphene composite material showed no weight gain, weight loss, stress corrosion, or cracking after 120 hours of testing. The organizational structure was intact, the physical and chemical indicators did not change, and the overall corrosion resistance time was extended by 24 hours, an extension of 25%.

[0109] Through simulated seawater erosion experiments, taking ordinary brass as an example, after adding Al, graphene and Mn, the corrosion resistance of the substrate in seawater is improved by 600%, from the original 0.0075mm-0.1mm / year corrosion rate to 0.00125mm-0.0166mm / year.

[0110] It can be seen that the composite material prepared by this implementation has good high temperature resistance and corrosion resistance, which can solve the high temperature corrosion problem of instruments and pipelines of some non-critical components in the aerospace field, and ensure the flight safety of aircraft. In high temperature components such as automobile engines and exhaust systems, the above optimized graphene brass alloy formula and surface oxide film production effectively improve the high temperature corrosion resistance of the substrate and extend the service life of the components. In addition, it also solves the high temperature corrosion problem in high temperature heat exchangers, boilers and other equipment in the energy field, extends the service life of the equipment, reduces the failure rate, and greatly ensures personal safety.

[0111] Embodiment 5

[0112] Different from the above embodiment, in this embodiment, the graphene composite profile contains the following raw material components in percentage by mass: Cu: 50-90%, Ni: 0.01-45%, Fe: 0.01-2%, Mn: 0.01-14%, P: 0.001-0.4%, graphene: 0.001-10%, and one or more of the trace elements Al, Si, S, Mg, Bi, As, Sb, Ag, and Au, and the total amount is less than 0.5%, and the balance is Zn.

[0113] Based on the above-mentioned component content requirements, the brass scrap selected in this embodiment is copper scrap with nickel (Ni) plated on the surface from social recycled materials, which is optimized for use, and C194 and C192 recycled materials are added at the same time.

[0114] This embodiment utilizes the good wettability of Ni element and graphene in the raw material, combined with the semi-solid stirring process, to homogenize the graphene structure that has been ball-milled and mixed. Since Ni element and graphene have good wettability, the added graphene and Ni element form a binary eutectic solid solution strengthening body, which plays a role in strengthening the matrix.

[0115] In the semi-solid process, the good wettability of Ni hard crystal core and graphene is utilized to continue to coat graphene around the periphery of Ni crystal core, thereby forming a crystal core with Ni element as the core, which effectively limits the growth of copper grains. Then, through the solid solution strengthening effect of Ni element, copper element and graphene, the Fe element in the matrix is ​​used to further refine the grains and strengthen the creep resistance of the material. Then, through the stirring and extrusion production process, a finer and strengthened organizational structure is obtained. With the support of graphene's own high strength and high conductivity, after later rolling and drawing, graphene forms a fibrous radial staggered organization in the organization along the rolling and extrusion direction and the radial extension direction, forming an efficient electron transmission channel, so that the problem of Fe and Ni elements deteriorating the conductivity can be improved.

[0116] At the same time, NIMn alloy can be formed by adding Mn element. Through precipitation strengthening of the alloy, the mechanical properties and corrosion resistance of the alloy can be effectively improved without affecting the conductivity. At the same time, the eddy current corrosion resistance of the substrate can be significantly improved.

[0117] Through experiments, it can be seen that this embodiment prepares a complex graphene copper alloy with high hardness, high temperature creep resistance, high conductivity and high strength. Compared with ordinary BZn15-20, when 0.02% graphene is added, its tensile strength is increased from 415MPa to 535.35MPa, an increase of 29%; Vickers hardness is increased from 180 to 246.6, an increase of 37%; yield strength is increased by 190%, and its value is increased from 256MPa to 486.4MPa.

[0118] Based on the above performance parameters, the graphene composite material prepared in this embodiment can be used in aerospace antenna brackets, support structures of thermal protection layers, shielded antennas for electronic communication equipment, pins for electronic integrated circuits and other fields, which greatly enhances the stability of structural parts, extends the service life of equipment and components in the above fields, and reduces replacement and maintenance costs.

[0119] Embodiment 6

[0120] Different from the above embodiment, in this embodiment, the graphene composite profile contains the following raw material components in percentage by mass: Cu: 50-97%, Fe: 0.1-1%, Sn: 0.01-5%, P: 0.001-0.4%, graphene: 0.001-10%, Zn: 3-49%, and the remainder is one or more of Mn, Au, Ag, Ni, Au, and Al, and the total amount is less than 0.5%.

[0121] Based on the above component content requirements, the brass waste selected in this embodiment is preferably recycled from the integrated circuit and chip industries, recycled lead legs and connector industry lead recycling materials, and added with Sn-containing recycled materials such as oil radiator radiator fins, etc., as raw materials for production. Its main purpose is to solve the problem of corrosion resistance of brass materials in all pipes and wires in contact with seawater, oil and gas, and equipment components in seawater environment.

[0122] This embodiment uses recycled brass Sn-plated recycled materials, adds graphene components, and uses a semi-solid fine grain stirring process to achieve the filling of graphene in the refined CuSnZn alloy grain structure. Through medium-temperature continuous extrusion curing, graphene forms a fibrous three-dimensional radial interlaced structure in the organization along the rolling and extrusion directions and the radial extension direction. The high conductivity of graphene eliminates the potential difference in the impurity elements, greatly reduces the cathode reduction reaction of the copper matrix in the seawater environment, and improves the corrosion resistance of the graphene composite material.

[0123] Due to the support of graphene fibrous radial interlaced structure, the microhardness of CuSnZn alloy is greatly improved. At the same time, the enhanced matrix structure produced by the mutual complementation of graphene and Sn atoms presents a fine-grained state, which increases the wear resistance and erosion resistance of the copper matrix in seawater.

[0124] Experiments show that the corrosion resistance of the copper material with graphene added in simulated seawater is 25 times higher than that of the copper alloy without graphene after mechanical polishing. This shows that graphene effectively blocks the penetration of Cl and oxygen into the copper matrix, making the corrosion inhibition efficiency of the graphene alloy reach more than 90%.

[0125] The results of erosion corrosion tests show that the critical flow velocity reaches 5.7 m / s compared with the critical flow velocity of 3 m / s for arsenic-aluminum marine brass, which exceeds the materials used in the existing mainstream marine environment and has outstanding erosion resistance.

[0126] Based on the above performance parameters, the graphene composite material prepared in this embodiment can solve the corrosion problem of components of various operating equipment such as sailing ships, deep-sea drilling platforms, offshore power plants, seawater desalination, purification plants, and all pipes and lines in contact with seawater, oil and gas, as well as the impact corrosion resistance of equipment parts in seawater environments. It not only greatly reduces the replacement and maintenance frequency of marine equipment and related components, but also reduces the maintenance cost of equipment in seawater environments, greatly improving the service life of the equipment.

[0127] The graphene composite profiles prepared based on the above embodiments can at least be applied to aircraft or connectors or automobile terminals or relays or conductive, elastic, supporting components in electrical, electrical and electronic fields or corrosion-resistant, highly elastic and highly conductive components in corrosive and high-temperature environments.

[0128] The above is a specific implementation of the embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of this application.

Claims

1. A graphene composite profile prepared from brass waste, characterized in that: The brass waste and graphene are processed by powder metallurgy combined with a medium-temperature continuous extrusion process to obtain the graphene composite profile; The graphene composite profile comprises the following raw material components in percentage by mass: Cu: 45-97%, P: 0.001-0.4%, Fe: 0.01-1%, graphene: 0.001-10%, Zn: 3-49%, and the remainder is one or more of Ag, Au, Ni, Sn, Mn, and Al, and the total amount is less than 0.5%; Or, the graphene composite profile comprises the following raw material components in percentage by mass: Cu: 45-97%, Ag: 0.0001-0.1%, Fe: 0.01-1.5%, P: 0.001-0.4%, graphene: 0.001-10%, Zn: 3-49%, and the remainder is one or more of Ni, Fe, Au, Sn, Mn, and Al, and the total amount is less than 0.5%; Or, the graphene composite profile comprises the following raw material components in percentage by mass: Cu: 50-97%, Mn: 0.001-5%, Al: 0.001-7.5%, Fe: 0.01-1%, P: 0.001-0.4%, graphene: 0.001-10%, Zn: 3-49%, and the remainder is one or more of Ni, Sn, Ag, and Au, and the total amount is less than 0.5%; Or, the graphene composite profile comprises the following raw material components in percentage by mass: Cu: 50-90%, Ni: 0.01-45%, Fe: 0.01-2%, Mn: 0.01-14%, P: 0.001-0.4%, graphene: 0.001-10%, and one or more of trace elements Al, Si, S, Mg, Bi, As, Sb, Ag, and Au, with a total amount less than 0.5%, and the balance being Zn; Or, measured by mass percentage, the graphene composite profile contains the following raw material components: Cu: 50-97%, Fe: 0.1-1%, Sn: 0.01-5%, P: 0.001-0.4%, graphene: 0.001-10%, Zn: 3-49%, and the remainder is one or more of Mn, Au, Ag, Ni, and Al, and the total amount is less than 0.5%.

2. The process for preparing a graphene composite profile using brass waste according to claim 1, characterized in that: The steps include: S1, selecting brass scraps containing different components according to the application scenarios of graphene composite profiles; S2, crushing the brass waste into brass block fragments; S3, according to the application scenario of the graphene composite profile, adding 0.001-10% by mass of graphene to the brass block fragments, and forming a first-size mixed powder liquid by wet ball milling; S4, subjecting the first-size mixed powder liquid to a semi-solid state rotation shear stirring process, so that the graphene is evenly filled in the brass fine crystal structure to form a graphene-brass mixed substrate; S5, heating the extrusion die cavity of the continuous extruder, and continuously extruding the graphene-brass mixed substrate when the graphene-brass mixed substrate is in a semi-liquid state, so that the graphene as a filling element is completely extruded into the lattice gap of the brass fine-grained structure to form a graphene composite profile blank that overcomes the point, line and surface defects of the brass; S6, processing the graphene composite profile blank with reference to the subsequent process of conventional brass profile to obtain a graphene composite profile, wherein after continuous extrusion and subsequent processes, a fibrous three-dimensional radial interlaced structure for efficient electron transmission is formed inside the graphene composite profile.

3. The process for preparing graphene composite profiles using brass waste according to claim 2, characterized in that: The size of the brass block fragments is 1-2 cm, and the particle size of the first-size mixed powder liquid is less than 50 μm.

4. The process for preparing graphene composite profiles using brass waste according to claim 2, characterized in that: The S4 comprises the following steps: S41, feeding the first-size mixed powder liquid into the front section of a circular feeder provided with an ultrasonic device, and performing a homogenization treatment on the first-size mixed powder liquid by utilizing the cavitation effect of the ultrasonic wave on the liquid; S42, feeding the first-size mixed powder liquid after homogenization treatment into the rear section of a circular feeder provided with a heating device, heating the circular feeder to 500-650° C. according to the copper content of the first-size mixed powder liquid, injecting inert gas into the rear section and keeping the temperature, so that the first-size mixed powder liquid reaches a semi-solid state to form a graphene-brass mixed substrate; S43, the graphene-brass mixed substrate is subjected to rotational shear stirring by a twin-screw rotating mechanism of a circular feeder, the screw stirring speed is 10r-400r / min, and after stirring for 10-20min, it is transported to the discharge port of the circular feeder.

5. The process for preparing graphene composite profiles using brass waste according to claim 4, characterized in that: The circular feeder is made of nickel-based high-temperature metal GH3044; the pushing pressure range of the twin screws is 50-65 MPa. At this time, the density of the graphene-brass mixed substrate is more than 65% of the normal solid theoretical density.

6. The process for preparing graphene composite profiles using brass waste according to claim 2, characterized in that: The S5 comprises the following steps: S51, sending the graphene-brass mixed substrate into a continuous extruder; S52, according to the ratio of copper and zinc in the brass waste, the extrusion cavity temperature of the continuous extruder is set to 800-950° C., so that the copper alloy is in a semi-liquid state in the extrusion cavity, the extrusion pressure is set to not less than 1000 MPa, and the graphene-brass mixed substrate is continuously extruded to obtain the graphene composite profile blank.

7. The process for preparing graphene composite profiles using brass waste according to claim 6, characterized in that: The continuous extruder is a Conform continuous extruder, and the extrusion die cavity is made of nickel-based high-temperature metal GH3044.

8. The process for preparing graphene composite profiles using brass waste according to claim 2, characterized in that: The subsequent processes include rolling and drawing.

9. The process for preparing graphene composite profiles using brass waste according to any one of claims 2 to 8, characterized in that: The graphene composite profile is a graphene composite copper bar, a graphene composite copper plate, a graphene composite copper strip, a graphene composite copper rod, a graphene composite copper wire or a graphene composite copper tube.

10. The graphene composite profile prepared according to any one of the preparation processes of claims 2-9 is applied to aircraft or consumer electronic connectors, data center connectors, new energy vehicle connectors or automotive circuit terminals or relays or electrical and electrical components that are conductive, elastic, and support components, or corrosion-resistant, highly elastic, and highly conductive components in corrosive and high-temperature environments.

Citation Information

Patent Citations

  • A method and application of preparing graphene composite copper strip using copper waste

    CN119140824B

  • Preparation method of graphene enhanced copper or copper alloy bars

    CN107267792A

  • Copper-based composite material with high strength, corrosion resistance and abrasion resistance

    CN108893647A

  • Preparation method of modified graphene reinforced composite material

    CN109207778A

  • Graphene-reinforced copper-based composite material and warm-pressing molding preparation method thereof

    CN112063873A

Cited By

  • Copper alloy with excellent high-temperature softening resistance and preparation method and application thereof

    CN120519735A

  • CuMnC composite material, hot pressing sintering preparation method and application of CuMnC composite material

    CN120700326A

  • High-uniformity ultra-fine grain brass alloy material and preparation method thereof

    CN122012982A

  • Aluminum-based graphene material and preparation method thereof

    CN122327035A